Obesity-Related Genes Expression in Testes and Sperm Parameters Respond to GLP-1 and Caloric Restriction - Ana S. Correia; Sara C. Pereira; Tiago Morais; Ana D. Martins; Mariana P. Monteiro; Marco G. Alves; Pedro F. Oliveira (Biomedicines, 2022)
Aim: Calorie restriction (CR) diets and glucagon-Like Peptide-1 (GLP-1) analogs are known to alter energy homeostasis with the potential to affect the expression of obesity-related genes (ORGs). We hypothesized that CR and GLP-1 administration can alter ORGs expression in spermatozoa and testes, as well as the sperm parameters implicated in male fertility. Materials and Methods: Six-week-old adult male Wistar rats (n = 16) were divided into three groups, submitted either to CR (n = 6, fed with 30% less chow diet than the control rats), GLP-1 administration (n = 5, 3.5 pmol/min/kg intraperitoneal) for 28 days, or used as controls (n = 5, fed ad libitum). Selected ORGs expression, namely the fat mass and obesity-associated (FTO), melanocortin-4 receptor (MC4R), glucosamine-6-phosphate deaminase 2 (GNPDA2), and transmembrane protein 18 (TMEM18) were evaluated in testes and spermatozoa by a quantitative polymerase chain reaction (qPCR). Results: CR resulted in lower body weight gain and insulin resistance, but a higher percentage of sperm head defects. GLP-1 administration, despite showing no influence on body weight or glucose homeostasis, resulted in a lower percentage of sperm head defects. CR and GLP-1 administration were associated with a higher expression of all ORGs in the testes. Under CR conditions, the genes FTO and TMEM18 expression in the testes and the MC4R and TMEM18 transcripts abundance in sperm were positively correlated with the spermatozoa oxidative status. The abundance of FTO and TMEM18 in the spermatozoa of rats under CR were positively correlated with sperm concentration, while the testes’ TMEM18 expression was also positively correlated with sperm vitality and negatively correlated with insulin resistance. Testes GNPDA2 expression was negatively correlated with sperm head defects. Conclusions: CR and GLP-1 administration results in higher ORGs expression in testes, and these were correlated with several alterations in sperm fertility parameters.